2008
DOI: 10.2304/elea.2008.5.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Judging Text Presented on Screen: Implications for Validity

Abstract: Technological innovation undoubtedly offers many potential benefits for education and the assessment of learning, which have been acknowledged elsewhere. One area that is relatively under-researched relates to the practice of how assessors interact with longer texts that are presented on screen. This is an important area of study because there might be moves to scan or digitally capture longer texts, such as essays or portfolios that contain long textual chunks, and to deliver them online to assessors. This us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Johnson and Greatorex (2008) argue that this issue might also affect those assessing longer texts on screen, implying a need to carry out studies exploring how judgements about longer textual performances might be influenced when assessors read them in different modes. This concern resonates with another recent screen marking study, which found correlations between re-marked essays to be significantly lower when those scripts were re-marked on screen compared with their re-mark on paper (Fowles, 2008).…”
Section: British Journal Of Educational Technologymentioning
confidence: 99%
“…Johnson and Greatorex (2008) argue that this issue might also affect those assessing longer texts on screen, implying a need to carry out studies exploring how judgements about longer textual performances might be influenced when assessors read them in different modes. This concern resonates with another recent screen marking study, which found correlations between re-marked essays to be significantly lower when those scripts were re-marked on screen compared with their re-mark on paper (Fowles, 2008).…”
Section: British Journal Of Educational Technologymentioning
confidence: 99%
“…The challenges relate mostly to the usability of the systems, e.g. judgements are impaired when moderators must manage different pages in documents [10]. Searching through different portfolios presents difficulties when viewing and comparing different candidates' work.…”
Section: Benefits and Challenges Of Emoderationmentioning
confidence: 99%
“…This article contributes to a growing research literature which explores how the technological environment (mode) in which marking is carried out influences marking processes (Price & Petre, 1997;Whetton & Newton, 2002;Royal-Dawson, 2003;Sturman & Kispal, 2003;Fowles & Adams, 2005;Fowles, 2008;Johnson & Greatorex, 2008;Coniam, 2009Coniam, , 2010Coniam, , 2011Johnson et al, 2009). Screen and paper-based marking modes each possess characteristics or 'affordances' (Gibson, 1979), and it is possible that these can affect both the manual and the cognitive processes involved in marking a text.…”
Section: Introductionmentioning
confidence: 99%
“…Johnson and Greatorex (2008) point out that there has been more consideration about how the reading of longer texts on screen affects students being assessed than there has about those who are responsible for marking such texts, although the issues for both groups should be synonymous. Very recently this balance has been slightly redressed by a number of studies (Fowles, 2008;Shaw & Imam, 2008;Coniam, 2009;Johnson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%